Salina wrote:

Hi Brent, Sorry but I still didn't get why f(8) is same as f(4)?

We're told that f(x) = f(x + 1)

So, f(4) = f(4 + 1)

In other words, f(4) = f(5)

Likewise, since f(x) = f(x + 1), we know that f(5) = f(5 + 1)

In other words, f(5) = f(6)

Keep going to see that f(4) = f(5) = f(6) = f(7) = f(8) = f(9) = ...etc

So, if f(4) = 17, then it is also true that f(5) = 17, f(6) = 17, f(7) = 17, f(8) = 17, f(9) = 17,...etc

Does that help?

Cheers,

Brent

_________________

Brent Hanneson – Creator of greenlighttestprep.com

Sign up for my free GRE Question of the Day emails